2010
DOI: 10.1111/j.1467-9450.2010.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Children’s word fluency strategies

Abstract: Two word fluency tasks, the FAS letter fluency task and the "animal" semantic fluency task, were administered to 130 healthy Swedish-speaking children between 6 and 15 years of age. The main aim was to gather normative data on these word fluency tasks for Swedish-speaking children. Another purpose was to examine the switching and clustering strategies used, along with the occurrence of erroneous responses, in relation to demographic data and number of words retrieved. Both phonological and semantic analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
69
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(97 citation statements)
references
References 21 publications
15
69
0
3
Order By: Relevance
“…In addition, phonemic analysis in the SVF task and semantic analysis in the PVF could also have been explored in order to adapt to the Brazilian context. International studies have also used this type of analysis when investigating the components of clustering and switching (Sauzéon et al, 2004;Tallberg et al, 2011). However, the adaptation of the method carried out in our study is the initial step to reinforce the use of PVF and SVF tasks, which is important to stimulate other researchers to further develop adaptations of appropriate methods for the Brazilian population.…”
Section: Final Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, phonemic analysis in the SVF task and semantic analysis in the PVF could also have been explored in order to adapt to the Brazilian context. International studies have also used this type of analysis when investigating the components of clustering and switching (Sauzéon et al, 2004;Tallberg et al, 2011). However, the adaptation of the method carried out in our study is the initial step to reinforce the use of PVF and SVF tasks, which is important to stimulate other researchers to further develop adaptations of appropriate methods for the Brazilian population.…”
Section: Final Considerationsmentioning
confidence: 99%
“…In terms of this variation, international studies have found significant differences in the SVF performance between 7-8 years old and 9-10 years old; whereas, when it comes to PVF, the number of words retrieved significantly increases starting at 11-12 years (Sauzéon, Lestage, Raboutet, Kaoua, & Claverie, 2004;Tallberg, Carlsson, & Liberman, 2011). The literature shows that both adults and children have a better performance in SVF tasks in comparison with PVF tasks (Sauzéon et al, 2004;Strauss et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Três escores estratégicos têm sido mais utilizados com adultos (Abwender, Swan, Bowerman, & Connolly, 2001) e crianças (Nieto, Galtier, Barroso, & Espinosa, 2008;Tallberg, Carlsson, & Lieberman, 2011;Takács, Kóbor, Tárnok, & Csépe, 2014): 1. Número de agrupamentos de palavras produzidas sucessivamente que compartilham características semânticas (pertencentes a uma subcategoria semântica) ou fonológicas (iniciadas ou terminadas com a mesma sílaba); 2.…”
unclassified